Extensive Use of Habitat-Damaging Fishing Gears Inside Habitat-Protecting Marine Protected Areas - Perry, Allison L.; Blanco, Jorge; García, Silvia; Fournier, Nicolas (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are critical for halting marine biodiversity loss and safeguarding ecosystems. However, efforts to designate additional areas as MPAs have generally taken precedence over ensuring that designated sites are effectively protected. Serious concerns exist about marine “paper parks” in Europe, particularly in relation to the threat of fishing. We focussed on 1,945 MPAs in EU and UK waters that are designated to protect habitats, and assessed the extent of fishing inside them with gears that are known to directly threaten those same habitats. Such “high-risk” fishing was widespread, occurring within 510 MPAs that represented 86% of the area assessed, and was more prevalent in larger, offshore sites. More intense high-risk fishing inside reef and sandbank MPAs was associated with the poorer conservation status of those habitats in countries’ waters. Our findings indicate that without systematic restrictions on damaging fishing gears, MPAs are unlikely to help reverse the ongoing declines of European marine habitats.